2008
DOI: 10.2202/1542-6580.1649
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer of Polymer Particles in Gas-Phase Polymerization Reactors

Abstract: In this paper the effects of particles configuration and particles distance on the heat transfer rate in a gas phase olefin polymerization reactor have been studied using the computational fluid dynamic (CFD) modeling approach. The goal was to determine the causes of particle overheating in this reactor. It has been shown that classic correlations such as Ranz-Marshall are sufficiently adequate when far away particles with no interactions are to be modeled. However, when particles are sufficiently close to hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The general conclusions were that local hydrodynamic conditions can be important, that conduction played a role in heat transfer even in a turbulent fluidised bed, and that (as expected) the conductivity of a solid surface with which a polymerising particle is in contact, also plays a role in the development of temperature profiles inside the growing polymer 13, 14. In a very similar effort, another group used essentially the same approach to reconfirm that particle/particle interactions can influence the observed particle heat transfer coefficient, but no attempt was made to look in detail at particle/surface interactions 16, 17…”
Section: Introductionmentioning
confidence: 98%
“…The general conclusions were that local hydrodynamic conditions can be important, that conduction played a role in heat transfer even in a turbulent fluidised bed, and that (as expected) the conductivity of a solid surface with which a polymerising particle is in contact, also plays a role in the development of temperature profiles inside the growing polymer 13, 14. In a very similar effort, another group used essentially the same approach to reconfirm that particle/particle interactions can influence the observed particle heat transfer coefficient, but no attempt was made to look in detail at particle/surface interactions 16, 17…”
Section: Introductionmentioning
confidence: 98%
“…McKenna et al, McKenna et al and Erickson and McKenna studied the effect of particle clustering on the evolution of temperature gradients, showing that particle clustering can cause the significant reduction of heat removal efficiency and additional increase of temperature gradients. Behjat et al evaluated the effect of particle concentration on gas–particle heat transfer rates in gas‐phase polymerization reactors, concluding that the increase of the particle concentration can lead to reduction of the gas–particle heat transfer coefficients, making analysis of heat transfer resistance even more important. Erickson et al investigated the interactions between the suspended polymer particles and the reactor walls, concluding that the internal reactor walls can also affect the thermal behavior of the growing polymer particles.…”
Section: Introductionmentioning
confidence: 99%
“…The detailed analysis of the particle proximity effects is beyond the scope of the present work and requires the use of stochastic procedures, because of the fast dynamics of suspended particle arrangements and broad size distributions of suspended polymer particles . Previous studies analyzed effects of particle clustering in polymerization media using CFD, using some fixed particle configurations to represent the system, which does not seem appropriate for analysis of suspended particles in the pneumatic section of the MZCR reactor. In general, these studies showed that particle clustering can lead to worse heat transfer conditions and to particle temperature rise.…”
Section: Introductionmentioning
confidence: 99%
“…Polymerization reactions are highly exothermic reactions. If the polymer temperature rises above the melting point, the polymer can melt and be a source of thermal agglomeration ( [25], [26]) and hot spots ( [27], [26], [28], [29]). On the other hand, if the temperature is too low then particles can become brittle producing unwanted fines that must be separated from the outlet gas.…”
Section: Introductionmentioning
confidence: 99%
“…Heat transfer plays an important role in polymer particle overheating. Behjat et al [25], Dehnavi et al [30], Mckenna et al [27] used CFD simulations to compute convective heat-transfer coefficients between polymer particles and the gas phase. They compared the single particle heat-transfer coefficient results with the Ranz-Marshall correlation and obtained good comparisons.…”
Section: Introductionmentioning
confidence: 99%